Effect of plant maturity stage on digestibility and distance walked for diet selection by goat at north Kordofan state, Sudan - Hag Abdel Moniem, M.A. El-; Hassabo, A.; Bushara, I.; O. Eisa, M.; A. Ishag, I. (Scientific Journal of Zoology, 2013)
The main objectivewas to study grazing behavior of goats; diet selection, nutritive value,digestibility of range plant and body gained at flowering and seed settingstage at September and November 2010 respectively in El-khuwei locality (ElRosa). A completely randomized design was used (CRD). Sampling was done by twostage flowering and seed sating stage were selected diets and feed intakelocating a 2000 x 2000 m plots. The average weights gains during the floweringand seed setting stage were 17 and 18.28kg respectively. Goats during theflowering stage was preference on bite counts of the different species, howeverhighly (P < 0.0001) at the flowering and least during the seed settingstage. Goat preference ranked Bano(Eragrostis tremula), Huskneet (Cenchrus biflorus), Difra (Echinocloa colonum),leflef (Luffa aegyptiaca), Gaw (Aristida spp.), Fisiya (Fimbristyls hispidula),Himeira (Hymenocardia acida),Nuida (Sida cordofolia), Tmrfar (Oldenlandia senegalensis) and Aboelrakhus(Andropogon gayanus), while Gadgad (Geigeriaalata), Buid (Commelinia subulata), Simeima (Sesamum alatum), Abodaib(Ceraotheca sesamoid) and Rabaa(Zalea spp) least than that. A significant higher (P < 0.001) goatsselective feed intake, in vitro dry matter digestibility, dry matter, organicmatter and crude protein higher at flowering stage and lowers during the seedsetting stage. However; ash contents and crude fiber of plants weresignificantly higher at the seed setting stage. Body weight gain wassignificantly highest during the flowering stage, while the distance walked bygoats for diet search was significantly longest during the seed setting stage. Itwas concluded that flowering stage beneficially goats highly preference andselectivity different species, feed intake and inviter dry matter digestibilityand body weight gained. The seed setting stage was highly ash contents, crudefiber distant walked.